KESEJAHTERAAN PSIKOLOGIS PENGHAFAL AL-QUR’AN PENYANDANG TUNANETRA - Yoga Achmad Ramadhan (Prodi Ilmu Administrasi Negara, 2019)
This Research aims to analyze and description of psychologicalwell-being of Al-Qur’an Memorizer who were blind. The research is aqualitative research with phenomenology study approach. Data collectionmethod used in this research was interview. Data analysis used in thisresearch was qualitative desriptive. Data realibility checking was done usingtriangulation technique. According to the research, there found thatpsychological wealth Al-Qur’an Memorizer where subject AB and SY are ableto accept themselves just the way they are, controlling warm relations withother to fit it with their needs, having purpose, and clear meaning of life, alsoaware and use their potential in continuous way.The increased ofpsychological well-being was obtained due to social support from family,friends and community. They both reported an increased psychologicalwell-being after they reached life goals dimension. This study revealed lifegoals as initial dimension that helped subjects to reach other dimensions ofpsychological well-being: self acceptance, independence, environmentmastery, personal growth, and positive relationships with others.